Upaya Bimbingan Belajar untuk Meningkatan Kualitas Belajar Anak di Desa Tirtomarto - Pebrianti, Chindi; Ambarawati, Mika; Wijayanti, Rina; Rochsun, Rochsun (JPM PAMBUDI, 2024)
This article aimed to help parents improve the quality of their children's education at home. Learning at home is an important focus. However, the preliminary study done in Tirtomarto Village showed children had low motivation to learn at home. Children tended to be lazy to study when they were with their parents. They said that studying at home tended to be boring. Therefore, it is hoped that tutoring can be a solution to help parents in the learning process at home. It is also expected that tutoring is expected can improve the quality of learning and motivation to learn.